Hexagonal structure hexapod robot: developing a method for omni-directional navigation - Billah, Md. Masum; Ahmed, Mohiuddin; Khan, Md. Raisuddin; Farhana, Soheli (2009)
In this paper, we propose a method that allows a hexapod robot to navigate omni-directionally with hexagonal structure. Typical body structures for hexapod robot are analyzed. Hexapod robot frequently navigates various directions over variety of surfaces. To enable locomotion in rough surface, hexapod must be able to stably move in any direction. A comparative study, based on different model of hexapod for omni-directional navigation, concludes that the hexagonal hexapod robot can be able to navigate omni-directionally on the complex surface. Finally, a method is developed for omni-directional navigation of the hexapod robot.